PENGEMBANGAN E-SCRAPBOOK BERBASIS CANVA PADA WEBSITE HEYZINE UNTUK HASIL BELAJAR MATERI SEL SMAN1 PEMATANGSIANTAR - Nur Wardany; Mastiur Verawaty Silalahi; Masni Veronika Situmorang (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: Science and Technology (IPTEK) has shown significant changes in the field of education, making the teaching and learning process more effective and interactive. Difficulties in learning are reflected in the minimal use of media during the learning process, which affects the quality of student achievement at SMA Negeri 1 Pematangsiantar. From the results of observations conducted, it was obtained that only 165 students out of 432 students received scores above the Minimum Completion Minimum (KKM). Based on the information above, this study aims to understand the feasibility of teaching media, student responses, and the value of learning outcomes after implementing e-scrapbooks. The research and development (R&D) model uses the ADDIE approach. The location of this research is SMA Negeri 1 Pematangsiantar and the period is from April to August 2025. The results of the product feasibility test based on expert validator standardization with 82.45%. All aspects are in the very good category. The results of student responses obtained through a questionnaire of 50.60% prove that most students expressed a favorable reaction to the implementation of e-scrapbook teaching media. The learning outcomes in the experimental class, as many as 29 students (90.90%) achieved a score above the KKM, while in the control class only 8 students (22.22%) completed The value of the non-parametric test results using Mann-Whitney, proves that the significance score of 0.00 is less than 0.05, indicating that Ho is rejected and Ha is accepted. Keywords: E-scrapbook; Heyzine;  Pematangsiantar; Cells. Abstrak: IPTEK (Ilmu Pengetahuan dan Teknologi) telah menunjukkan perubahan signifikan pada bidang pendidikan, menjadikan proses belajar mengajar lebih efektif dan interaktif. Kesulitan dalam pembelajaran tercermin dari minimnya penggunaan media selama proses pembelajaran, yang memengaruhi kualitas prestasi siswa di SMA Negeri 1 Pematangsiantar. Dari hasil pengamatan yang dilakukan diperolah bahwa yang mendapat nilai diatas KKM hanya 165 siswa dari 432 siswa. Berdasarkan keterangan diatas penelitian ini bertujuan untuk memahami kelyakan media ajar, respon tanggapan siswa, dan nilai hasil belajar sesudah menerapkan e-scrapbook. Model penelitian pengembangan atau Research and Development (R&D) memakai pendekatan ADDIE. Lokasi riset ini di SMA Negeri 1 Pematangsiantar serta jangka waktu bulan April sampai Agustus 2025. Hasil uji kelayakan produk berdasarkan standardisasi validator ahli dengan 82,45%. Seluruh aspek tersebut berada pada kategori sangat baik. Hasil respon siswa diperoleh melalui angket sebanyak 50,60% membuktikan kebanyakan peserta didik menyampaikan reaksi menguntungkan terhadap penerapan media ajar  e-scrapbook. Nilai hasil belajar di kelas eksperimen, sebanyak 29 siswa (90,90%) mencapai nilai di atas KKM, sementara di kelas kontrol hanya 8 siswa (22,22%) yang tuntas. Nilai hasil uji non-parametrik menggunakan Mann-Whitney, membuktikan skor nilai signifikansi 0,00 lebih kecil 0,05  menandakan Ho ditolak dan Ha diterima. Kata kunci: E-scrapbook; Heyzine; Pematangsiantar; Sel.